Oral administration of the probiotic strain Lactobacillus helveticus BGRA43 reduces high-fat diet–induced hepatic steatosis in mice and restores gut microbiota composition - Teofilović, Ana; Vratarić, Miloš; Bursać, Biljana; Gligorovska, Ljupka; Vojnović Milutinović, Danijela; Stanisavljević, Nemanja; Strahinić, Ivana; Mišić, Danijela; Nikolić, Filip; Pavlović, Bojan; Jončić Savić, Katarina; Aydogan, Cem; et al. (Frontiers in Pharmacology, 2025)
IntroductionThe prevalence of metabolic dysfunction-associated steatotic liver disease (MASLD) is rapidly increasing. Modulation of the gut microbiota through the use of probiotics has been recognized as an important option for the treatment of hepatic steatosis. Previous studies suggested that the bacterial strain Lactobacillus helveticus BGRA43 (LHBGRA43) can reduce inflammation and improve the bacterial balance in the gut. The aim of this study was to investigate whether oral administration of LHBGRA43 in mice fed a high-fat diet contributes to the reduction of hepatic steatosis through its beneficial effects on the composition of the gut microbiota.MethodsMale C57BL/6J mice (2.5 months old) were divided into three groups: a control group fed a standard diet (10% kcal fat), a high-fat diet (HFD) group (60% kcal fat for 14 weeks) and a HFD group that received freeze-dried LHBGRA43 dissolved in PBS orally for the last 5 weeks of the diet.ResultsHistological analysis of the liver showed that animals fed HFD exhibited hepatic steatosis, while no lipid droplets were present in the liver of animals receiving LHBGRA43. This decrease in steatosis correlated with decreased level of sterol regulatory element-binding protein-1c, reduced expression of the fatty acid transporter Cd36, enzymes involved in ceramide synthesis and proinflammatory markers. The administration of LHBGRA43 also improved the integrity of the small intestine barrier, as evidenced by an increased level of ZO-1 protein. The observed reduction in intestinal permeability was associated with a decreased Firmicutes/Bacteroidota ratio and increased abundance of the genera Alistipes, Acetatifactor and Odoribacter, as well as a decreased concentration of branched-chain 4-methylvaleric acids.DiscussionIn conclusion, the restoration of the gut microbiota composition in combination with the strengthening of the small intestine barrier suggests that LHBGRA43 could be used as a general probiotic strain with ameliorative effects on hepatic lipid accumulation and lipotoxicity.